1987
DOI: 10.1111/j.1600-0528.1987.tb00489.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fibre optic transillumination with clinical and radiographic caries diagnosis

Abstract: Fibre optic transillumination (FOTI) has been employed during the course of a 3-yr clinical dentifrice trial which initially involved 3003 children. At the initial examination, a subgroup of 813 13-yr-olds, and at the following annual visit, 2247 14-yr-olds, were examined using a 150 W lamp and 0.5 mm diameter probe. Routine clinical and radiographic examinations were performed separately. Compared to the clinical scores for anterior teeth, FOTI detected an additional 64% of interproximal lesions at the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 6 publications
3
28
0
1
Order By: Relevance
“…The additional diagnostic yield from FOTI was 40.0% compared to CVE alone; this is of the same order as that reported by Stephen et al [1987]. The number of dentine lesions not diagnosed by FOTI but diagnosed by CVE was also similar in both studies at under 10%.…”
Section: Discussionsupporting
confidence: 75%
“…The additional diagnostic yield from FOTI was 40.0% compared to CVE alone; this is of the same order as that reported by Stephen et al [1987]. The number of dentine lesions not diagnosed by FOTI but diagnosed by CVE was also similar in both studies at under 10%.…”
Section: Discussionsupporting
confidence: 75%
“…By FOTI, on average less than one fourth of the number of carious lesions detected by visual and radiographic examination were reported. Compared to radiography this result corresponds to results reported by Mitropoulos [1985] and Stephen et al [1987]. If a shadow seen in the dentine was used as a sign of cavitation, the average sensitivity and positive predictive value was found to be 0.04 and 0.33, respectively.…”
Section: Discussionsupporting
confidence: 68%
“…The increase in sensitivity was caused by the fact that the majority of shadows reported were assessed to be confined to enamel only. From other studies it has been demonstrated that the extent of caries lesions in general are assessed to be less profound by FOTI than by radiography [Mitropoulos, 1985;Stephen et al, 1987], and in this investigation the same seemed to be the case as the lesions detected in enamel by FOTI were assessed to be in the dentine on the bitewing radiographs. On the basis of the low sensitivity and positive predictive value obtained by FOTI, it seems to be obvious that this method should not be the method of choice for the identification of approximal surfaces with cavitated carious lesions.…”
Section: Discussionsupporting
confidence: 60%
“…Several clinical di agnostic methods have been devised to utilise the appear ance of a white spot as a measure o f the extent o f caries. Fibre-optic transillumination methods [Purdell-Lewis and Pot, 1974;Peltola and Wolf, 1981;Stephen et al" 1987;Holt and Azevedo, 1989;Longbottom and Pitts, 1990] are sim ple, non-invasive techniques that can be used as clinical car ies diagnosis methods. Light-scattering methods have also been devised in which a bright white light source is directed onto a small area of enamel surface, and the scattered radi ation is measured [ten Bosch et al, 1984].…”
mentioning
confidence: 99%